Attenuated Listeria monocytogenes as a Vaccine Vector for the Delivery of OMPW, the Outer Membrane Protein of Aeromonas hydrophila - Zeng, Haijuan; Xie, Manman; Ding, Chengchao; Ma, Junfei; Xu, Dongpo; Wang, Xiang; Qiu, Jingxuan; Liu, Qing (Frontiers in Microbiology, 2020)
Listeria monocytogenes (LM) is a gram-positive facultative intracellular pathogen that could stimulate host to produce inflammatory response, cell-mediated immunity, and humoral immunity. In this study, an attenuated live vector vaccine for Aeromonas hydrophila (AH) named EGDeABdd-dat-ompW was successfully constructed using an attenuated vector named EGDeABdd, in which dal, dat, actA, and inlB genes were deleted from wild-type LM-EGDe. To construct EGDeABdd-dat-ompW, a recombinant plasmid pERL3-dat-ompW obtained by inserting the dat gene from EGDe and outer membrane protein gene ompW from AH into pERL3 plasmid was transformed into EGDeABdd cell. The safety and immunogenicity of EGDeABdd-dat-ompW as an attenuated vector vaccine for delivery of OMPW were assessed through analyzing invasion to Caco-2 cells and mice, cytokine production of macrophagocyte and mouse splenocytes, and T-cell proliferation of mouse splenocytes. Serum titers against AH and the immunoprotective effect of the vaccine to mice were also measured after intravenous injection with vaccine for four times. The results showed that the live vector vaccine EGDeABdd-dat-ompW for AH exhibited high attenuation in invading Caco-2 cells and mice than did EGDe. Real-time PCR (RT-PCR) showed that cytokines (e.g., TNF-α, IL-6, and IL-1β from macrophages; and IL-6 and IFN-γ from mouse splenocytes) had significantly increased after immunization by EGDeABdd-dat-ompW. Meanwhile, the vaccine could induce the production of CD3+CD4+ and CD3+CD8+ T-cell proliferation of mice and generate effective immunoprotection against lethal challenge of 20 × LD50 AH. All these results indicated that the attenuated EGDeABdd-dat could be used as a live vector for the delivery of the exogenous gene, not only possessing safety but also providing high immunogenicity. The successful application in the AH vaccine further showed that it could be used in other fields such as vaccines in cancer or infectious diseases.